Pengaruh Konsumsi Buah jeruk (Citrus reticulata) dan Suplementasi Zinc terhadap Kadar Glukosa Darah Puasa pada Wanita Diabetes Melitus Tipe 2 - Amalia Purwandari; JB Suparyatmo; Sugiarto Sugiarto (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: Patients with Diabetes Mellitus (DM) Type 2 are at risk of micronutrient loss related to metabolic diseases, one of them is zinc. It plays an important role since it affects the function of pancreatic cell β, insulin activities, glucose homeostasis and pathogenesis of DM. Low zinc levels are associated with higher complications of DM. One of the nutrients that helps absorbing zinc is organic acids such as citric acid and ascorbic acid contained in citrus fruits.Objective: to analyze the effect of citrus fruits (Citrus reticulata) and zinc supplements consumption on fasting blood glucose in women with DM Type 2.Method: This study was an experimental study using pretest and posttest method with control group. The subjects were 30 people with DM Type 2 in Prolanis club in three Puskesmas in Surabaya who had been selected using consecutive sampling, and divided into 2 groups, namely the treatment group that consumed 200 g of orange and 20 mg of zinc supplement per day and the control group that consumed only 20 mg zinc per day. Citrus fruits and zinc supplements were consumed daily for four weeks. Fasting blood glucose was analyzed using automatic chemistry analyzer. Data analysis included univariate analysis with Shapiro-Wilk and bivariate analysis with Independent t-test, Mann-Whitney and Paired t-testResults: Fasting blood glucose in the subjects consuming citrus fruits and zinc supplements was decreased by 16.67 mg/dl (from 155.87 mg/dl to 139.20 mg/dl) (p = 0.121), while the group with zinc consumption was decreased by 9.85 mg/dl (from 140.93 mg/dl to 131.13 mg/dl) (p = 0.095). The decrease in fasting blood glucose in both groups was not statistically significant.Conclusion: Consumption of citrus fruits and zinc supplements did not significantly reduce fasting blood glucose in women with DM Type 2. Further research is needed with a longer period of intervention to better reflect the changes in zinc metabolism related to blood glucose control.ABSTRAKLatar Belakang : Pasien Diabetes Mellitus (DM) Tipe 2 beresiko kehilangan zat gizi mikro terkait metabolik penyakitnya, salah satunya adalah zinc. Zinc berperan penting karena mempengaruhi fungsi sel β pankreas, aktifitas insulin, homeostasis glukosa dan patogenesis DM. Kadar zinc yang rendah terkait dengan komplikasi DM yang lebih tinggi. Salah satu zat gizi yang membantu penyerapan zinc adalah asam organik seperti asam sitrat dan asam askorbat yang terkandung dalam buah jeruk.Tujuan : Menganalisa pengaruh konsumsi buah jeruk (Citrus reticulata) dan suplementasi zinc terhadap kadar gula darah puasa wanita DM tipe 2.Metode : Rancangan berupa quasi eksperimental dengan metode pretest and posttest with control group. Jumlah subjek 30 orang wanita DM tipe 2 anggota klub Prolanis di 3 Puskesmas di Kota Surabaya yang dipilih secara consecutive sampling, terbagi dalam 2 kelompok yaitu kelompok perlakuan yang mengkonsumsi 200 gram jeruk dan suplementasi zinc 20 mg/hari serta kelompok kontrol hanya mengkonsumsi zinc 20 mg/hari. Intervensi dilakukan 4 minggu. Gula darah puasa dianalisa menggunakan automatic chemistry analizer. Analisis data meliputi univariat dengan Shapiro-Wilk, analisa bivariat meliputi Independent t-test dan Mann-Whitney.Hasil : Meskipun rata-rata penurunan gula darah puasa sebesar 16,67 mg/dl pada subjek yang mengkonsumsi jeruk dan suplementasi zinc (p=0,121), namun tidak signifikan secara statistik.Kesimpulan : Konsumsi buah jeruk dan suplementasi zinc tidak signifikan menurunkan gula darah puasa wanita DM Tipe 2. Diperlukan penelitian lanjutan dengan jangka waktu intervensi yang lebih lama.